Distribution of Margalefidinium polykrikoides red tide in the Strait of Hormuz and the Persian Gulf using satellite remote sensing - Samad Hamzei; Emad Koochaknejad (بوم‌شناسی آبزیان, 2023)
In this study, the MODIS satellite imaging sensor, which is a sensor with a visible band of 36 and an infrared band, was used to produce satellite images of water surface temperature and chlorophyll-a in the Pesrian Gulf and Oman Sea. In addition, field measurements of phytoplankton species density were performed to investigate the pattern of dispersal of red tide events during 2008–2009. Finally, the effect of the current and temperature on the dispersal and expansion of the red tide in the Strait of Hormuz and the Persian Gulf was investigated. Satellite images showed that the M. polykrikoides's red tidal expansion path in the Persian Gulf and Gulf of Oman was in line with the overall water circulation path in the Persian Gulf. In the Gulf of Oman, the structure of oceanic meso-scale eddies has also played a role in red tide dispersion, and it helps to disperse the red tide to the Strait of Hormuz and adjacent Iranian coastal waters in the Persian Gulf. Moreover, the results of this study showed that decreasing water temperature increased the intensity of the red tidal phenomenon.